2006
DOI: 10.1007/s11434-006-2139-4
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structures of the oxygenated diamond (100) surfaces

Abstract: By means of first principles method on the basis of density functional theory (DFT), the equilibrium geometries and density of states (DOS) of the two oxygenated diamond (100) surfaces, bridging model and on-top model are calculated. The results indicate that there are no surface states located in the band gap of the bridging model of oxygenated diamond (100) surface, and the occupied surface states in the valence band are attributed to the non-bonded O 2p orbital, O 2p and C 2p bonding orbitals, and C 2p and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 29 publications
(32 reference statements)
2
14
0
Order By: Relevance
“…When the surface is covered by a monolayer of H atoms, the length of C─C bond increases dramatically to 1.61 Å, 0.23 Å longer than that of the clean surface. The results are quite consistent with those obtained in previous reports . It further confirms the accuracy of the diamond surface model constructed in our work.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…When the surface is covered by a monolayer of H atoms, the length of C─C bond increases dramatically to 1.61 Å, 0.23 Å longer than that of the clean surface. The results are quite consistent with those obtained in previous reports . It further confirms the accuracy of the diamond surface model constructed in our work.…”
Section: Resultssupporting
confidence: 93%
“…For the O‐terminated diamond films, studies have shown that the splicing structure will transform into the bridging structure . At room temperature, the main configuration of the O‐terminated diamond films is the cyclic ether structure . The two common configurations of the NH 2 ‐terminated diamond films are the bridging structure and the splicing structure.…”
Section: Methodsmentioning
confidence: 99%
“…Though the method of CVD is used to grow gem-diamond crystals [7][8][9][10], the technology of synthesis is not perfect. Among these methods, the TGM under static high pressure is thought to be the most effective to grow large and good-quality diamond crystals of more than two millimeters (0.1 ct).…”
mentioning
confidence: 99%
“…With the rapid improvement of computer power, the simulation by theoretical calculations may compensate for the limits of experimental studies. Actually, the theoretical studies of NH 3 , O 2 , CO and O adsorption on Ir, Al, Rh, Cu metal surfaces and non-metallic diamond surface have been extensively carried out [20][21][22][23][24][25] . The simulation method of theoretical calculations also becomes an indispensable method for studying the metal/solution interfacial structure [26,27] .…”
mentioning
confidence: 99%